Peningkatan Kapabilitas Aparatur Desa dalam Penyusunan Kebijakan Kesehatan Berbasis Masyarakat di Desa Lubuk Siam, Kabupaten Kampar - Randika, Rendi; Redho, Ahmad; Hasrianto, Nofri (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The low capacity of village officials to develop health policies based on evidence and the real needs of the community is a challenge in village health development. This community service activity aims to improve the knowledge, attitudes, and skills of Lubuk Siam Village officials in designing health policies that are participatory, systematic, and responsive to local conditions. The target group includes village heads, village officials, health cadres, and community representatives. The methods used include counseling, training, group discussions, simulations, and technical assistance in drafting policy documents. The activity was carried out in a participatory manner at the Lubuk Siam Village Office on July 2, 2025. Evaluation results showed significant improvements in all aspects, namely knowledge, attitudes, and skills of participants. Before the activity, the majority of participants were in the fair to poor category in terms of understanding and skills in policy development. However, after the activity, most participants experienced an increase to the good and very good categories. This activity demonstrates that an applicable and collaborative science and technology-based approach can increase the capacity of village human resources in formulating more inclusive and data-driven health policies. This is a strategic step in encouraging the creation of sustainable village health governance.